2007
DOI: 10.1300/j136v11n04_02
|View full text |Cite
|
Sign up to set email alerts
|

A Window into Our Patron's Needs

Abstract: This article provides an analysis of transcripts of chat reference transactions. The data analyzed for this study were from 631 chat reference transcripts from the University of Minnesota Libraries-Twin Cities Campus collected from January to May for both 2003 and 2004. Specifically, the patrons' statuses, the length of sessions, the type of chat transactions, and the types of questions asked were examined. The findings determined that though a majority of patrons seeking assistance from the chat reference ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…23 This is further illustrated in a study by Houlson, McCready, and Pfahl in which analysis of 631 chat transcripts across different academic library user groups revealed that "How to Find" questions were the main type of question being asked via online chat for undergraduates (24 percent, n = 24), graduate students (10 percent, n = 36), and staff (7 percent, n = 28). 24 Two other categories, however, stand out for each user group within this study. Undergraduates' second and third top categories were "Subject Specific" (in-depth questions about a particular research topic) (17 percent, n = 66) and "Do You Own" questions (5 percent, n = 20).…”
Section: Are Particular Types Of Reference Mediums Better Suited For mentioning
confidence: 99%
“…23 This is further illustrated in a study by Houlson, McCready, and Pfahl in which analysis of 631 chat transcripts across different academic library user groups revealed that "How to Find" questions were the main type of question being asked via online chat for undergraduates (24 percent, n = 24), graduate students (10 percent, n = 36), and staff (7 percent, n = 28). 24 Two other categories, however, stand out for each user group within this study. Undergraduates' second and third top categories were "Subject Specific" (in-depth questions about a particular research topic) (17 percent, n = 66) and "Do You Own" questions (5 percent, n = 20).…”
Section: Are Particular Types Of Reference Mediums Better Suited For mentioning
confidence: 99%
“…One solution to this problem has been to create dual‐level categorization schemes that allow for greater flexibility and generalization of user need. Both DeGroote et al (2005) and Houlson (2006) used two‐tiered approaches in defining queries, with a result that we see with greater transparency the schemes in operation. Though at a high level many of the results are similar to some of what we have seen – Houlson's (2006) most‐used “how to find” and “do you own” categories mirror Marsteller and Kibbee's findings that known item searches predominate – understanding that the known item is most likely to be a journal article gives a “window” into user needs and, as DeGroote et al (2005) points out, may point to a need for targeted “instructional programs … to address those areas that generate the most confusion” (p. 451).…”
Section: Literature Reviewmentioning
confidence: 97%
“…A final refinement of this literature, has also come through the use of more sophisticated analysis tools to understand the data present in the transcripts. Houlson (2006) used a relational database to extract relationships between high‐ and low‐level queries, subject matter, and departmental affiliation. DeGroote et al (2005) used cross tabulation methods via SPSS to correlate user status, subject area, and general and specific question areas.…”
Section: Literature Reviewmentioning
confidence: 99%